Sectoral decomposition of convergence in labor productivity: A re-examination from a new dataset - Alistair Dieppe; Hideaki Matsuoka (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
This paper investigates how the sector-specific source or the changing sectoral composition of labor productivity has contributed to Ø-convergence, using a newly constructed eightsector database. The main findings are twofold. First, both within and sectoral reallocation have become important drivers of Ø-convergence in labor productivity. Second, agricultural productivity growth has been a significant contributor to Ø-convergence, whereas catch-up in other sectors has only contributed a small amount to convergence. The strong growth of the agriculture sector has been the most important driver of aggregate productivity convergence even though agricultural productivity itself in low-income countries is not converging to that in advanced economies.
urn:nbn:fi:bof-202204081133
Keywords: O1; O11; O4; 330; Labor productivity; Shift-share decomposition; Ø-decomposition; New sectoral database